Pteroceras dalaputtuwa (Orchidaceae: Epidendroideae: Vandeae: Aeridinae), a new species from Sri Lanka and re-collection of Pteroceras viridiflorum after 150 years - Priyadarshana, Tharaka S.; Atthanagoda, Anusha G.; Wijewardhane, Ishara H.; Siriweera, Kawshalya S.; Aberathna, Nimantha; Kumar, Pankaj (Phytotaxa, 2019)
Pteroceras dalaputtuwa, a new species, is described from the lowland-wet zone of Sri Lanka. For the first time in the history of plant nomenclature, a new species is named after an elephant, ‘Galgamuwa Dala Puttuwa’, which was killed for its majestic ivory. The new species shows a close morphological affinity with P. philippinense from the Philippines. However, P. dalaputtuwa sp. nov. can be readily distinguished by having small and partially opened flowers (10 mm long × 5 mm wide), short petals (4 mm long × 1 mm wide), short sepals (4.9 mm long × 3.0 mm wide) and elongated rectangular-oval spur (7 mm long × 3 mm wide). P. viridiflorum, which is considered as a “Critically Endangered Possibly Extinct” [CR(PE)] orchid, is also re-collected after after a gap of nearly 150 years with a record of a new colour form (white colour variant) and, is re-described with designation of a lectotype and an epitype.